PENGARUH SELF EFFICACY TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SD DALAM PEMBELAJARAN DARING - Pramesthi Ningrum; Rina Dyah Rahmawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Recently, education has been faced with learning that is not only carried out offline but also carried out online. Online learning has even been implemented since elementary education. This of course affects student learning outcomes. This study aims to determine the effect of self-efficacy on elementary students' mathematics learning achievement in online learning. This study used a quantitative survey method and was carried out on fourth grade elementary school students in Cluster II, Pleret Bantul District, consisting of 5 schools located in the sub-district area. The population in this study was 203 students and a sample of 132 students, with the technique used in sampling is proportional random sampling. Data collection techniques used are questionnaires and documentation. While the data analysis technique in this study used simple regression analysis with the help of SPSS 24.0. The results of the study concluded that there was a positive and significant influence between self-efficacy on elementary mathematics learning achievement in online learning. Data analysis resulted in a t-count value of 5.785 with a significance of 0.000, it was obtained t-table = 1.978 which can be seen from t-count > t table = 5.785 > 1.978 and a significance value of 0.000 <0.05.